Antimicrobial activity of Desplac® oral gel in the subgingival multispecies biofilm formation - Bueno-Silva, Bruno; Kiausinus, Karyne Rossit; Gonçalves, Francisco Jeferson dos Santos; Moreira, Marcus Vinícius Cintra; Oliveira, Eder Gonzaga de; Brugnera Junior, Aldo; Feres, Magda; Figueiredo, Luciene Cristina (Frontiers in Microbiology, 2023)
This study aimed to evaluate the antimicrobial effect of DESPLAC® product (composed of Aloe Vera, Propolis Extract, Green Tea, Cranberry, Calendula and Saccharin) on the subgingival bio-film. Two different protocols treated the 33-species biofilms: A) 2x/day (12/12h) for 1 minute with DESPLAC® or Noplak Toothpaste (Chlorhexidine + Cetylpyridine Chloride) or Oral B ProGingiva (stannous Fluoride) or a placebo gel; B) during 12 hours with the product DESPLAC® or 0.12% chlorhexidine gel or a placebo gel. After seven days of biofilm formation, the metabolic activity (MA) and biofilm profile were determined by 2,3,5-triphenyltetrazolium chloride and Checker-board DNA-DNA hybridization, respectively. Statistical analysis used the Kruskal-Wallis test, followed by Dunn's post-hoc. In protocol A, all treatments presented reduced MA compared to placebo (p≤0.05). The DESPLAC-treated biofilm showed a similar microbial profile to other antimicrobials, although with higher bacterial total counts. In protocol B, MA of DESPLAC-treated biofilms was minor than placebo’s MA but higher than chlorhexidine-treated biofilms (p≤0.05). Pathogen levels in DESPLAC-treated biofilms were smaller than in placebo-treated biofilms and elevated than in chlorhexidine-treated biofilms (p≤0.05). The DESPLAC® inhibited the biofilm development and disrupted the mature subgingival biofilm, highlighting its effect on Tannerella forsythia counts.